1986
DOI: 10.1002/jcp.1041280307
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural studies of the intracellular translocation of endocytosed alpha‐foetoprotein (AFP) by cytochemistry and of the uptake of 3H‐arachidonic acid bound to AFP by autoradiography in rat rhabdomyosarcoma cells

Abstract: A covalent conjugate of alpha-foetoprotein (AFP) and horseradish peroxidase (HRP) has been used to follow, at the ultrastructural level, the pathway of AFP uptake and translocation in a rat rhabdomyosarcoma cell line. The cells were incubated for several times at 4 degrees C and/or 37 degrees C, and fixed. AFP-HRP was found to enter the cells via coated pits and receptosomes and to move to tubular elements of the trans-reticular portion of the Golgi. Some observations suggest that AFP can be recycled back to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…ceptor binding but prevents endocytosis (34). Next, the cells were incubated at 37°C, which triggers endocytosis of receptorbound fetuin (35). As shown in Fig.…”
Section: Fig 2 Two-dimensional Sds-page and Western Blotting Of Promentioning
confidence: 99%
“…ceptor binding but prevents endocytosis (34). Next, the cells were incubated at 37°C, which triggers endocytosis of receptorbound fetuin (35). As shown in Fig.…”
Section: Fig 2 Two-dimensional Sds-page and Western Blotting Of Promentioning
confidence: 99%
“…AFP may compete with albumin for binding in different cell types [15,[27][28][29]. Cytochemical and kinetic studies, carried out in several tumoral cells as well as in normal human T lymphocytes [18,27,30,31] have shown that the AFP was taken up by a receptor-mediated endocytosis mechanism similar to that reported for transferrin [19,28,31].…”
Section: Introductionmentioning
confidence: 99%
“…After three washes with cold PBS, cells were fixed for 15 min at 4°C, in 1.6% glutaraldehyde prepared in 0.1 M cacodylate buffer, pH 7.2. Afterwards, they were washed and incubated with diaminobenzidine (Sigma) substrate as previously described [19]. Postfixation in 2% OsO 4 in cacodylate buffer, for 40 min at room temperature, dehydration in ethanol and embedding in Epon were carried out in situ.…”
Section: Binding and Uptake Of Afp Albumin-and Transferrin-hrp Conjumentioning
confidence: 99%
See 1 more Smart Citation
“…Immature cells from most fetal structures internalize afp, and it has been suggested that the purpose of that internalization-and one of the functions of this protein-is to transport and deliver polyunsaturated fatty acids into fetal cells 6,7 . The afp uptake ceases when embryonic cells and tissue structures approach a high degree of differentiation, even if the blood concentration of afp is still high or increasing [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%